A Highly Efficient Graphene Gold Based Green Supercapacitor Coin Cell Device for Energy Storage - Vivas, Leonardo; Singh, Dinesh Pratap (Frontiers in Energy Research, 2022)
Inclination to exploit renewable energy and their potential storage by facile, cost effective and ecofriendly way are exactly what the current alternative energy research is looking for. The high-performance supercapacitor devices made up with the electrode materials synthesized by simple and greener method are in utmost demand to achieve the goal of widespread commercialization. Keeping these points in view, one pot green synthesis of active electrode material rGO-Au composite is achieved which not only perform as a very good supercapacitor in three-electrode configuration but also demonstrates extremely well as a coin cell device, ready to use. Ascorbic acid; commonly found in citrus fruits plays an important role to reduce, graphene oxide into rGO and simultaneously gold salt into gold nanoparticles, resulting into rGO-Au composite. The maximum recorded specific capacitance by CV measurement is 303.02 Fg-1 at a scan rate of 5 mVs-1. Hindrance in the commercialization is caused by the differences in the supercapacitor performances between three electrode configuration and finally proposed device. Here the proposed coin cell device exhibits maximum areal and mass specific capacitance of 62.43 mFcm-2 and 56.09 Fg-1 respectively, that is very high among all reported graphene based composite devices benefitted over with commercially viable high capacity retention up to 80% even after 10000 cycles. The proposed device demonstrates high energy density ( ED = 7.79 Wh/Kg) comparable to Batteries and an optimum Power density ( PD = 2512.9 W/Kg) close to supercapacitor insinuating it an effective green supercapacitor for commercialization.